SAE Technical Paper Series 2018
DOI: 10.4271/2018-01-0384
|View full text |Cite
|
Sign up to set email alerts
|

Cylinder Deactivation for Increased Engine Efficiency and Aftertreatment Thermal Management in Diesel Engines

Abstract: D iesel engine cylinder deactivation (CDA) can be used to reduce petroleum consumption and greenhouse gas (GHG) emissions of the global freight transportation system. Heavy duty trucks require complex exhaust aftertreatment (A/T) in order to meet stringent emission regulations. Efficient reduction of engine-out emissions require a certain A/T system temperature range, which is achieved by thermal management via control of engine exhaust flow and temperature. Fuel efficient thermal management is a significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 12 publications
3
21
0
Order By: Relevance
“…Figure 7 illustrates the gas exchange during two-cylinder operation wherein both valve motion and fuel injection are deactivated for cylinders 1, 2, 5 and 6. A detailed discussion and results from three-cylinder operating strategy are outlined in Ramesh et al 25…”
Section: Methodsmentioning
confidence: 99%
“…Figure 7 illustrates the gas exchange during two-cylinder operation wherein both valve motion and fuel injection are deactivated for cylinders 1, 2, 5 and 6. A detailed discussion and results from three-cylinder operating strategy are outlined in Ramesh et al 25…”
Section: Methodsmentioning
confidence: 99%
“…Ramesh et al demonstrated the thermal management benefit of complex aftertreatment temperature control in a certain system temperature range, which could meet stringent emission regulations. Aftertreatment temperature is a significant consideration to achieve the best conversion efficiency [5]. There are also many researchers who have made efforts to study and optimize the exhaust gas temperature on aftertreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Cylinder deactivation (CDA) is one of the means to achieve elevated engine-outlet temperatures in a fuel-efficient manner, at low-load diesel engine operation. 9,1219 CDA is currently being implemented in production predominantly in gasoline vehicles. Diesel engine CDA is being investigated; however, as of 2018, there are no production system applications in ground vehicles.…”
Section: Introductionmentioning
confidence: 99%